# Bài 75 trang 40 SGK Toán 9 tập 1

##### Hướng dẫn giải

Sử dụng công thức: $$\sqrt {AB} = \sqrt A .\sqrt B \,\,\left( {A \ge 0,B \ge 0} \right)$$

Lời giải chi tiết

a)

\eqalign{ & \left( {{{2\sqrt 3 - \sqrt 6 } \over {\sqrt 8 - 2}} - {{\sqrt {216} } \over 3}} \right).{1 \over {\sqrt 6 }} \cr & = \left[ {{{\sqrt 6 \left( {\sqrt 2 - 1} \right)} \over {2\left( {\sqrt 2 - 1} \right)}} - {{6\sqrt 6 } \over 3}} \right].{1 \over {\sqrt 6 }} \cr & = \left( {{{\sqrt 6 } \over 2} - 2\sqrt 6 } \right).{1 \over {\sqrt 6 }}\cr& = \left( {\frac{{\sqrt 6 }}{2} - \frac{{4\sqrt 6 }}{2}} \right).\frac{1}{{\sqrt 6 }} \cr & = \left( {{{ - 3} \over 2}\sqrt 6 } \right).{1 \over {\sqrt 6 }} \cr & = - {3 \over 2} = - 1,5 \cr}

b)

\eqalign{ & \left( {{{\sqrt {14} - \sqrt 7 } \over {1 - \sqrt 2 }} + {{\sqrt {15} - \sqrt 5 } \over {1 - \sqrt 3 }}} \right):{1 \over {\sqrt 7 - \sqrt 5 }} \cr & = \left[ {{{\sqrt 7 \left( {\sqrt 2 - 1} \right)} \over {1 - \sqrt 2 }} + {{\sqrt {5 }\left( {\sqrt 3 - 1} \right)} \over {1 - \sqrt 3 }}} \right]:{1 \over {\sqrt 7 - \sqrt 5 }} \cr & = \left( { - \sqrt 7 - \sqrt 5 } \right)\left( {\sqrt 7 - \sqrt 5 } \right) \cr & = - \left( {\sqrt 7 + \sqrt 5 } \right)\left( {\sqrt 7 - \sqrt 5 } \right) \cr & = - \left( {7 - 5} \right) = - 2 \cr}

c)

\eqalign{ & {{a\sqrt b + b\sqrt a } \over {\sqrt {ab} }}:{1 \over {\sqrt a - \sqrt b }} \cr & = {{\sqrt {ab} \left( {\sqrt a + \sqrt b } \right)} \over {\sqrt {ab} }}.\left( {\sqrt a - \sqrt b } \right)\cr&= \left( {\sqrt a + \sqrt b } \right).\left( {\sqrt a - \sqrt b } \right) \cr & = a - b \cr}

d)

\eqalign{ & \left( {1 + {{a + \sqrt a } \over {\sqrt a + 1}}} \right)\left( {1 - {{a - \sqrt a } \over {\sqrt a - 1}}} \right) \cr & = \left[ {1 + {{\sqrt a \left( {\sqrt a + 1} \right)} \over {\sqrt a + 1}}} \right]\left[ {1 - {{\sqrt a \left( {\sqrt a - 1} \right)} \over {\sqrt a - 1}}} \right] \cr & = \left( {1 + \sqrt a } \right)\left( {1 - \sqrt a } \right) = 1 - a \cr}